Dynamic capital structure and political patronage: the case of Malaysia - Ebrahim, M. Shahid; Girma, Sourafel; Shah, M. Eskandar; Williams, Jonathan (Elsevier, 2014)
This paper investigates the effect of political patronage on firms' capital structure. The evidence is from Malaysia, a country characterised by relationship-capitalism, and covers 1988 to 2009. Using a system GMM estimator we find firms set leverage targets and adjust towards them following deviations at the rate of 28% per annum. Next, we construct a natural experiment and use a difference-in-differences model to investigate if the strategic financing decisions of politically patronised firms differ from non-connected firms after an exogenous shock caused by the 1997 Asian crisis. Our results unambiguously demonstrate a significant difference in the capital structure of patronised firms relative to non-connected firms following the exogenous shock but only for the crisis period 1998–2001. After 2002 the capital structures of patronised and non-connected firms are statistically equivalent.